In Which Conditions is Conservative Tratment Likely to Fail in Humeral Shaft Fractures? A Retrospective Analysis of 67 Patients - ALBAYRAK, Mehmet; UĞUR, Fatih (Galenos Yayinevi, 2023)
Aim:Humeral shaft fractures are one of the most common fractures of the upper extremity. Most humeral shaft fractures can be treated conservatively, but in some cases, surgical treatment is required. In this study, the characteristics of patients who needed surgical intervention due to unsuccessful conservative treatment and inability to achieve union were investigated.Materials and Methods:Data of 67 patients [female (n=41) and male (n=26)] in whom conservative treatment was initiated due to humeral shaft fracture were evaluated retrospectively. The data of the patients in whom treatment had to be switched to surgery during the follow-up period were analyzed. Age, gender, trauma type, fracture site and vitamin D levels on the day of the fracture were noted.Results:At the end of 54 (42-77) days, the treatment was switched to surgery due to nonunion in 14 patients. All of these patients were female, over the age of 60 years, and the humeral fractures in these patients were in the middle third of the humerus. The mean 25(OH) vitamin D [25(OH) D] level of these patients was 14 mg/dL (4-22 mg/dL).Conclusion:It is concluded that the conservative treatment is prone to fail if humeral shaft fracture is a proximal oblique or a mid-shaft one, if the patient is over the age of 60 years and female, and if 25(OH)D level of the patient is low.
Keywords: surgery; conservative; R; Medicine; humerus fracture